Mathematical modeling for the control of fly-borne mastitis disease in cattle - Adeyemi, Moses Olayemi; Oluyo, Temitayo Olabisi (Frontiers in Applied Mathematics and Statistics, 2023)
Several diseases cause losses in cattle farming, especially in the dairy industry among which mastitis disease (Bovine mastitis) is the leading cause of health and economic damages globally as it results in animals’ ill-health as well as reduced quality and quantity of milk produced by infected cows. Some mathematical researches have been conducted which focused on mastitis transmission from one udder-quarter to another in an infected cow, even though clinical researches established also cow-cow and flies-cow transmissions. The present work therefore proposed a mathematical model for the control of mastitis disease in cattle in the presence of flies as vectors. The formulated model was shown to have non-negative solutions in feasible regions for both cattle and flies’ populations. Further, the model has a stable disease-free equilibrium if the effective reproduction numbers are less than unity, and possibility of multiple endemic equilibria if otherwise. The numerical results indicated that the infectious populations can be reduced if the rates of the control parameters are increased, thereby curtailing or eradicating mastitis in cattle population.